Multimodal kidney‐preserving approach in localised and locally advanced high‐risk upper tract urothelial carcinoma. Issue 1 (11th October 2021) - Alhalabi, Omar; Campbell, Matthew T.; Xiao, Lianchun; Adriazola, Ana C.; Wilson, Nathaniel R.; Siefker‐Radtke, Arlene O.; Corn, Paul G.; Zurita, Amado; Jonasch, Eric; Gao, Jianjun; Adibi, Mehrad; Kamat, Ashish M.; et al.
Abstract: Objectives: Multimodal kidney‐preserving (MKP) strategies may be an option for patients with localised or locally advanced high‐risk upper tract urothelial carcinoma (UTUC) who have a relative contraindication for nephroureterectomy (NU). Materials and methods: We studied patients with UTUC who were managed with MKP strategies, consisting of systemic anticancer therapy, with or without local/topical strategies after endoscopic control of intraluminal tumours. Primary end points were overall survival (OS) and progression‐free survival (PFS). Results: Fourteen patients received MKP treatment between August 2013 and April 2020. Median baseline estimated glomerular filtration rate was 43 mL/min/1.73m 2 . MKP was mainly pursued to avoid dialysis (10/14, 71%), followed by low performance status and/or comorbidities (2/14, 14%). All patients had received systemic therapy: chemotherapy (64%) and immunotherapy (36%). Endoscopic control and/or laser ablation was feasible in 7 (50%) patients. Calculated overall risk of non‐organ confined disease was 35%. Predicted 2‐year and 5‐year relapse‐free probability (RFP) was 74% (24–92%) and 62% (10–85%), respectively. Median follow‐up was 31 months (95% CI: 22.6, NE), median OS was 48.1 months (95% CI: 48.1, NE) and 2‐year OS probability was 0.89 (95% CI: 0.71, 1). Median metastases‐free survival was 48.1 months (95% CI: 26.8, NE), median PFS was 22.4 months (95% CI: 15.6, NE) and 2‐year PFS probability was 0.48 (0.26, 0.89). Conclusion: Management of high‐risk localised or locally advanced UTUC with MKP strategies was associated with good tolerance, preservation of renal function, and comparable PFS and OS to predicted in vulnerable patients. Prospective studies with more patients are needed to evaluate these possible benefits relative to current standards.